Parameter sensitivity analysis and structural optimization of PLC construction method pile cofferdam based on RSM - Zhongchu Tian; Ye Dai; Shiyao Wang; Wei Zhang (PLoS ONE, 2025)
To explore the influence patterns of various structural parameters of the PLC construction method pile cofferdam on its mechanical properties, and to optimize the structural design for enhancing engineering safety and economy, this study relied on the PLC construction method pile cofferdam of the Luoxizhou Super Bridge. Multiple sensitivity analysis methods were employed to identify sensitive parameters. Subsequently, a multi-objective optimization study was conducted based on the identified sensitive parameters. Additionally, the entropy weight TOPSIS decision-making approach was introduced to quantify the advantages and disadvantages of each optimized scheme and the initial design scheme. The results indicate that: (1) Sensitivity rankings derived from the single parameter method and the response surface methodology are consistent across parameters, but the response surface methodology provides more accurate sensitivity quantification. (2) The thicknesses of the steel sheet pile wall, steel pipe pile wall, and bottom-sealing concrete significantly affect the maximum displacement and maximum stress of the cofferdam. (3) The entropy-weighted TOPSIS decision-making can effectively evaluate the advantages and disadvantages of the Pareto solution set optimized by the NSGA-II algorithm. (4) Economic cost and structural performance exhibit a nonlinear synergy: As cost increases, the maximum displacement of the cofferdam decreases markedly, whereas the maximum stress of the bottom-sealing concrete decreases at a slower rate.